Importance of the body for the bereaved family: beliefs, rituals and feelings that might interfere in the organ donation - Barros, Daniela (2020)
Death is a phenomenon that is invariably present in the daily lives of all families. Only human beings, of all living beings, know that they will die. The family plays a mediating role in the health-disease process as a health maintainer and, in the disease, participating in the healing, rehabilitation and death process. Therefore, the events of a natural and accidental order with one of the members affected by the family body and the possibility of breaking a bond due to death causes intense emotional, psychological and spiritual disruption. Like marriage, death is also a ritualized act. The funeral itself functions as a rite of passage that helps the family to internalize and accept death. The mourners begin the rites of separation from the dead where they remain until they feel ready for the suspension of mourning and social reintegration. The funerals and other rituals related to death serve to contextualize the experience. Devotion to care for the corpse reveals the anxiety that death causes and the attempt of the mourners to seek comfort and acceptance. In this context, we analyze how the relationship with the body of the deceased relative, considering all the funeral rituals and the mourning itself, can interfere in the family's decision to donate the organs or not. The literature shows that, among the families interviewed, 15.7% of the total refused to donate, and 17.6% of these emphasized the desire to keep the body intact. Another reason cited by family members in refusing to donate was the time it takes to return the body to start the funeral processions, which is about 24 hours. The family refusal to donate organs is permeated by legal, moral, ethical and religious issues. However, although we need to increase the authorizations for organ donation and, thus, allowing the continuation of unknown lives, it is necessary to respect the decision of each family, taken in the context of their repertoire.